Pemahaman Generasi Z terhadap Sighat Taklik: Studi Kasus di Kabupaten Sambas - Asman, Asman (Tasyri' : Journal of Islamic Law, 2025)
This study discusses the understanding of millennial brides of Generation Z towards sighat taklik after ijab kabul in brides and grooms who carry out weddings at the Sambas Religious Affairs Office, West Kalimantan. The understanding of millennial brides about sighat talik in KUA is that every millennial bride and groom after carrying out ijab kabul, especially men (husbands), some recite sighat taklik and some do not pronounce sighat taklik whose manuscript is in the marriage book. From this case, the pros and cons of the bride and groom after ijab kabul arise, so the question arises whether the pronunciation of sighat taklik is an obligation or not?. The focus of this research is how millennial brides of generation Z understand sighat taklik after ijab kabul at KUA Sambas, West Kalimantan?. The method in this study is to use a qualitative field approach while the approach in this study uses phenomenology. The findings in this study from eight respondents interviewed, namely the bride and groom, four of the bride and groom did not know the existence of sighat taklik and did not pronounce sighat taklik and four bride couples knew and pronounced the sighat taklik in the marriage book. The conclusion in this study is the occurrence of pros and cons to the sighat taklik in the marriage book, the lack of emphasis on socialization from the BP4 in the premarital material to the prospective bride and groom, and the lack of knowledge of the bride and groom in the affirmation of knowledge of the Marriage Law No. 1 of 1974, article 29 of the marriage agreement, and the understanding of the Compilation of Islamic Law article 46 concerning taklik talaq.